SUBSTANCE AND FUNCTIONAL PURPOSE OF FINANCIAL SECTOR OF NATIONAL ECONOMY - Барановський , Олександр (Socio-economic relations in the digital society, 2019)
Importance of scientific interest to problems of creation and development of financial sector of national economy is substantiated. Advantages and disadvantages of financial sector functioning in financial systems of different types are determined. Approaches of scientists to defi nition of substance and functional purpose of financial sector of national economy are critically analyzed. Treatment of financial sector as a system of economic relations, sphere or part of economy, part of real sector, service area, determinant of economic growth, complex of facilities, dedicated self-organized sub-system of financial system, complex of financial instruments, complicated system, non-material industrial factor is presented. It is stressed on system-wide characteristics of financial sector such as structure, integrity, non-additivity, limitation. hierarchy, territory segmentation, motivation, justifi cation, conjuncture, subjectivity, functionality. Author’s view of financial sector of national economy substance is presented. Author’s classifi cation of types of financial sector of national economy is presented. Views on correlation of financial sector of national economy and financial markets and financial system are reviewed. Shadow banking system is characterized.
Keywords: financial sector; types of financial sectors; functions of financial sector; structure of financial sector; financial system; financial market